Konsep Pra-Nikah Dalam Al-Qur’an: Kajian Tafsir Tematik - Ahmad Arifuz Zaki (Jurnal Bimas Islam, 2017)
The high rate of divorce in Indonesia one of them is caused by the lack of knowledge possessed by the community related to how to choose a good and ideal partner. This study aims to explore more deeply related to the criteria of the ideal partner in accordance with the Qur'an. This research is a qualitative research that is literature (library research). Source of data used is primary and secondary source. The primary sources are from al-Qur'an and secondary sources derived from the Shofwah at-Tafsir by Ali al-Shabuni, Tafsir al-Mizan by Al-Thaba'thaba'i, Tafsir al-Sya'rawi by al- Sya'rawi, Tafsir al-Azhar by Hamka and Tafsir al-Misbah by Quraish Shihab. The results of this study found that the criterias of choosing a good partner is a same faithful, opposite type, not mahram, good personality, has the nature of responsibility and have a vision in getting a marriage Tingginya angka perceraian di Indonesia salah satunya disebabkan oleh minimnya pengetahuan yang dimiliki oleh masyarakat terkait bagaimana cara memilih pasangan yang baik dan ideal. Penelitian ini bertujuan untuk menggali lebih dalam terkait kriteria-kriteria pasangan yang ideal sesuai dengan al-Qur’an. Penelitian ini merupakan penelitian kualitatif yang bersifat kepustakaan (library research). Sumber data yang digunakan adalah sumber primer dan sekunder. Sumber primer berasal dari al-qura’an dan sumber sekunder berasal dari kitab tafsir yang berupa Shofwat at-Tafsir karya Ali al-Shobuni, Tafsir al-Mizan karya Al-Thaba’thaba’i, Tafsir al-Sya’rowi karya al-Sya’rowi, Tafsir al-Azhar karya Hamka dan Tafsir al-Misbah karya Quraish Shihab. Hasil penelitian ini didapatkan bahwa kriteria memilih pasangan yang baik yaitu seiman, berlawanan jenis, bukan mahram, berkepribadian baik, memiliki sifat tanggung jawab dan memiliki visi dalam menjalani sebuah pernikahan